Capacitance response of concave well substrate touch-mode capacitive pressure sensor: Mathematical analysis and simulation. (August 2021) - Kang, MyongChol; Ri, Chan; Choe, JongHuan
Abstract: Touch mode capacitive pressure sensor (TMCPS) is focused due to its advantages of good linearity, mechanical robust and large overload protection for harsh industrial environment. This paper proposes a concave well-shaped substrate bottom electrode for further improvement of capacitance response of TMCPS. Small deflection model is utilized for mathematical analysis of proposed design and ANSYS and MATLAB software are utilized for simulation. The simulation result is compared with analysis and the excellent agreements predict the accuracy of analytical modeling. The sensitivity of proposed TMCPS is increased as 1.36 times as in operating pressure range from 0.25 to 2 ​MPa and the linear region of it is expanded as 2.60 times as the normal (flat substrate) one in touch mode, respectively. The analysis and simulation results indicate a significant improvement of sensitivity and linearity in touch mode. The analytical modeling and overall results will be helpful to design TMCPS for performance improvement and predict the behavior of it. Highlights: Concave well substrate touch mode capacitive pressure sensor (TMCPS) is proposed to improve performance of it. Analysis and simulation of capacitance response of the sensor is done. The sensitivity of the proposed sensor is higher than the normal one (flat substrate TMCPS). The linear region of the proposed sensor is expanded compare to the normal one.